The Importance of Preschool Children’s Portfolios in Kosovo and Their Meaning for Elementary School Teachers - Hajrullahu, Adelina; Sylaj, Vlora (Acta Paedagogica Vilnensia, 2023)
As a transition country, Kosovo faces many problems and challenges, especially in the field of the preschool education. As an issue of the early childhood education, among the new forms of child labor documentation, the portfolios are mentioned. Teachers build a rich picture of each child, combining strategies such as using the traditional tools of child study (for example, observations, anecdotal records, checklists) with newer documentation technologies such as photos, portfolios, and recorded conversations (New & Cochran, 2007). Purpose of this research was to gather data from preschool teacher, school teachers and parents regarding the children’s portfolios: the children portfolio in the preschool? How important are they for the primary school and for the parents? What the content? re some of issues that we research with this article.
Keywords: portfolio; early education; transition; teacher; preschool